Depression and contemporaneity: psychoanalysis as a form of treatment from a reading of Byung-Chul Han - Sanvesso, Lucas Koltun (2024)
The alarming increase in cases of depression today makes it an urgent matter to be debated. The Theoretical research, as well as the dialogue between different fields of knowledge on the topic is a way to advance its understanding. The research intends to obtain an overview of depression today, and from this perspective, to propose psychoanalysis as a treatment method for depression. Through textual and argumentative comparison of the works from the philosopher Byung-Chul Han and lacanian´s psychoanalysis theory scholars, the search approaches the contemporary subject as a product of neoliberal ideals, influenced by values based on a market logic. Depression, seen from this perspective, is an effect of social organizers, and the contemporary context of subjective formation signals for the continued increase in the number of depression cases. Faced with this, psychoanalysis proves to be a possible treatment method for this depressive subject.